DOMESTIC VIOLENCE AND WOMEN EMPOWERMENT IN JALINGO LOCAL GOVERNMENT AREA OF TARABA STATE, NIGERIA (Abuja Journal of Sociological Studies, 2026)
This study assessed domestic violence and women empowerment in Jalingo local government area of Taraba state, Nigeria. The specific objectives of the study were to: ascertain the causes of domestic violence against women, examine the forms of domestic violence against women, assess the effects of domestic violence against women and low women empowerment and suggest possible solutions to curtail/reduce incidence of domestic violence against women and low women empowerment. The study used socialist/radical feminism theory as its theoretical framework. The survey research design was adopted for this study using the questionnaire and key informant instruments to collect data from respondents. Findings for the study revealed that drug and alcoholic abuse by husbands due to family issues such as suspicion and infidelity by their wives, traditions and culture when restricting wives over certain responsibilities and activities, poverty due to unemployment and illiteracy affecting household income are causes of domestic violence. Also, it was revealed in the study that certain cultural practices where women are denied of inheritances leads to low women empowerment. The study also discovered that domestic violence causes low self-esteem to the women who affect their empowerment status, domestic violence affect development of personality of the children negatively, domestic violence affects women affection for the men counterparts and most young women who witness domestic violence tend to fear marriage. Based on these findings, the study recommends that, the government should enforce legal sanction against perpetrators of domestic violence, the relevant authorities should promote girl-child education, the government should empower women/girls financially to be self-sustainable in all ramifications, and re-orientation of the family members on the gains of cordial relationships among couples and the need to empower women.